Communication strategy in socialising analogue switch off in North Sulawesi - Angeline Lydia Kojansow; Leviane Jackelin Hera Lotulung; Johnny Semuel Kalangi (Faculty of Communications Science, Dr. Soetomo University, 2023)
This research delves into the efficacy of the North Sulawesi Broadcasting Commission's communication strategy in facilitating the analogue switch-off programme. The study employs qualitative research methods, utilising in-depth interviews with key stakeholders, and adopts Hafied Cangara's communication strategy framework, based on Laswell's theory , to analyse the Commission's approach. The outcomes reveal that the Commission's communication plan effectively conveyed the intended message to the public. It achieved its objectives of disseminating information and educating the populace about the switch-off process. Nonetheless, the plan could have been further enhanced to better address the diverse needs and concerns of the audience. The findings offer valuable insights into the challenges and opportunities associated with implementing the analogue switch-off programme, especially concerning formulating efficient communication strategies that can effectively reach all segments of Society. By shedding light on these aspects, this research significantly contributes to the broader discourse on digital television and its profound influence on broadcasting policies in Indonesia.